Ambient melting behavior of stoichiometric uranium oxides - Burakovsky, Leonid; Ramsey, Scott D.; Baty, Roy S. (Frontiers in Nuclear Engineering, 2024)
As UO 2 is easily oxidized during the nuclear fuel cycle it is important to have a detailed understanding of the structures and properties of the oxidation products. Experimental work over the years has revealed many stable uranium oxides including UO 2 , U 4 O 9 (UO 2.25 ), U 3 O 7 (UO 2.33 ), U 2 O 5 (UO 2.5 ), U 3 O 8 (UO 2.67 ), and UO 3 , all with a number of different polymorphs.These oxides are broadly split into two categories, fluorite-based structures with stoichiometries in the range of UO 2 to UO 2.5 and less dense layered-type structures with stoichiometries in the range of UO 2.5 to UO 3 . While UO 2 is well characterized, both experimentally and computationally, there is a paucity of data concerning higher stoichiometry oxides in the literature. In this work we determine the ambient melting points of all the six stoichiometric uranium oxides listed above and compare them to the available experimental and/or theoretical data. We demonstrate that a family of the six ambient melting points map out a solid-liquid transition boundary consistent with the high-temperature portion of the phase diagram of uranium-oxygen system suggested by Babelot et al.